Synthesis and characterization of push-pull molecules bearing tetrafluorobenzene central acceptor modified with two peripheral hexyloxy and dihexylamino donors - Ramaiyan, Manikannan; Kulhánek, Jiří; Bureš, Filip (University of Pardubice, 2014)
Starting from 1,4-diiodotetrafluorobenzene or 1,4-bis(5-bromothiophene-2- yl)tetra-fluorobenzene, four new push-pull molecules were synthesized via twofold cross-coupling reactions. Suzuki-Miyaura and Sonogashira reactions were employed to gain access to target molecules. The central tetrafluorobenzene acceptor unit was modified by two peripheral N,N-dihexylamino and Ohexyloxy groups with different donating ability to generate quadrupolar D-π-A- π-D system with tailored intramolecular charge-transfer. The length, planarity and composition of the π-linker between the acceptor and donors was modified by combination of 1,4-phenylene, 2,5-thienylene and acetylenic subunits in order to finely tune the linear as well as nonlinear optical properties.